TRACKING THE HISTORICAL DEVELOPMENT OF KEDATUAN SAWITTO IN SOUTH SULAWESI IN THE XVI-XVII CENTURY - Hasaruddin, Hasaruddin; Mania, Sitti; Yani, Ahmad; Musyarif, Musyarif (Jurnal Adabiyah, 2021)
This paper aims to understand the existence of Kedatuan Sawitto particularly its historical development and its social and political role in the XVI-XVII Century. To discuss this problem, the researchers used historical research methods that are based on data collection which include: heuristics, criticism, interpretation, and historiography. The results showed that the XVI century AD was the heyday of   Kedatuan Sawitto. At the beginning of the sixteenth century the  Kedatuan Sawitto succeeded in establishing a strong and influential maritime force on the western coast of Sulawesi Island. Kedatuan Sawitto succeeded in conquering a number of areas on the west coast of the Sulawesi and several areas in the inland Sulawesi. Among the conquered territories were Bonto-Bonto, Bantaeng, Segeri, Lemo-Lemo, Passokkoreng, Baroko, Toraja, Mamuju, Kaili and Toli-Toli. The control of the area is of course for economic interests, namely to control shipping and trade along the western coast of the Sulawesi. The glory of Kedatuan Sawitto ended when the Kedatuan Sawitto was conquered by the Gowa kingdom which replaced the position of the Kedatuan Sawitto as the controller of shipping and trade on the west coast of Sulawesi.Keywords: History; Kedatuan Sawitto; XVI-XVII Century الملخصتهدف هذه الورقة إلى تحديد وجود Kedatuan Sawitto في القرنين السادس عشر والسابع عشر ، لا سيما التنمية والدور الاجتماعي والسياسي لكيداتوان ساويتو. لمناقشة هذا الأمر ، يستخدم المؤلفون أساليب البحث التاريخية التي تستند إلى جمع البيانات ، بما في ذلك: الاستدلال والنقد والتفسير والتأريخ. أظهرت النتائج أن القرن السادس عشر الميلادي كان ذروة مملكة ساويتو. في بداية القرن السادس عشر ، نجحت مملكة ساويتو في تأسيس قوة بحرية قوية ومؤثرة على الساحل الغربي لجزيرة سولاويزي. تمكنت Kedatuan Sawitto من احتلال عدد من المناطق على الساحل الغربي لجزيرة سولاويزي والعديد من المناطق في الداخل. من بين الأراضي المحتلة كانت بونتو بونتو ، وبانتاينج ، وسيجيري ، وليمو ليمو ، وباسوكورينج ، وباروكو ، وتوراجا ، وماموجو ، وكايلي ، وتولي تولي. السيطرة على المنطقة لأغراض اقتصادية ، وهي السيطرة على الشحن والتجارة على طول الساحل الغربي لجزيرة سولاويزي. انتهت ذروة مجد مملكة ساويتو عندما غزاها مملكة غوا التي حلت محل مملكة ساويتو بصفتها المتحكم في الشحن والتجارة على الساحل الغربي لسولاويزي.كلمات مفتاحية: التاريخ؛ كيداتوان ساويتو القرنين السادس عشر والسابع عشر.ABSTRAKTulisan ini bertujuan untuk mengetahui eksistensi Kedatuan Sawitto Abad XVI-XVII khususnya perkembangan dan peran sosial dan politik Kedatuan Sawitto. Untuk membahas hal tersebut, maka peneliti menggunakan metode penelitian sejarah yang mendasarkan diri pada pengumpulan data, meliputi: heuristik, kritik, interpretasi, dan historiografi. Hasil penelitian menunjukkan bahwa abad XVI Masehi menjadi periode kejayaan Kedatuan Sawitto. Pada permulaan abad XVI Kedatuan Sawitto berhasil membentuk kekuatan maritim yang kuat dan berpengaruh di pesisir barat Pulau Sulawesi. Kedatuan Sawitto berhasil menaklukkan sejumlah wilayah di pesisir barat Pulau Sulawesi dan beberapa wilayah di pedalaman. Di antara wilayah taklukkan tersebut adalah Bonto-Bonto, Bantaeng, Segeri, Lemo-Lemo,  Passokkoreng, Baroko, Toraja, Mamuju, Kaili dan Toli-Toli. Penguasaan wilayah tersebut untuk kepentingan ekonomi yakni mengontrol pelayaran dan perdagangan di sepanjang pesisir barat Pulau Sulawesi. Puncak kejayaan Kedatuan Sawitto tersebut berakhir ketika ditaklukkan oleh Kerajaan Gowa yang menggantikan posisi Kedatuan Sawitto sebagai pengontrol pelayaran dan perdagangan di pesisir barat Sulawesi.